Fate of tenogenic differentiation potential of human bone marrow stromal cells by uniaxial stretching affected by stretch-activated calcium channel agonist gadolinium - Nam, H.Y.; Raghavendran, H.R.B.; Pingguan-Murphy, Belinda; Abbas, A.A.; Merican, A.M.; Kamarul, Tunku (Public Library of Science, 2017)
The role for mechanical stimulation in the control of cell fate has been previously proposed, suggesting that there may be a role of mechanical conditioning in directing mesenchymal stromal cells (MSCs) towards specific lineage for tissue engineering applications. Although previous studies have reported that calcium signalling is involved in regulating many cellular processes in many cell types, its role in managing cellular responses to tensile loading (mechanotransduction) of MSCs has not been fully elucidated. In order to establish this, we disrupted calcium signalling by blocking stretch-activated calcium channel (SACC) in human MSCs (hMSCs) in vitro. Passaged-2 hMSCs were exposed to cyclic tensile loading (1 Hz + 8% for 6, 24, 48, and 72 hours) in the presence of the SACC blocker, gadolinium. Analyses include image observations of immunochemistry and immunofluorescence staining from extracellular matrix (ECM) production, and measuring related tenogenic and apoptosis gene marker expression. Uniaxial tensile loading increased the expression of tenogenic markers and ECM production. However, exposure to strain in the presence of 20 μM gadolinium reduced the induction of almost all tenogenic markers and ECM staining, suggesting that SACC acts as a mechanosensor in strain-induced hMSC tenogenic differentiation process. Although cell death was observed in prolonged stretching, it did not appear to be apoptosis mediated. In conclusion, the knowledge gained in this study by elucidating the role of calcium in MSC mechanotransduction processes, and that in prolonged stretching results in non-apoptosis mediated cell death may be potential useful for regenerative medicine applications.